Goat's milk against malaria - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
In a couple of years, your herd of goats could be able to supply the entire population of Africa with a vaccine against malaria. Numerous research efforts around the world, all seeking the remedy against malaria, are on the brink of breakthroughs....